Is Peritonitis Risk Increased in Elderly Patients on Peritoneal Dialysis? Report from the French Language Peritoneal Dialysis Registry (RDPLF). Issue 3 (May 2016) - Duquennoy, Simon; Béchade, Clémence; Verger, Christian; Ficheux, Maxence; Ryckelynck, Jean-Philippe; Lobbedez, Thierry
Introduction: This study was carried out to examine whether or not elderly patients on peritoneal dialysis (PD) had an increased risk of peritonitis. Methods: This was a retrospective cohort study based on data from the French Language Peritoneal Dialysis Registry. We analyzed 8, 396 incident patients starting PD between January 2003 and December 2010. The end of the observation period was 31 December 2012. Patients were separated into 2 age groups: up to 75 and over of 75 years old. Results: Among 8, 396 patients starting dialysis there were 3, 173 patients older than 75. When using a Cox model, no association was found between age greater than 75 years and increased risk of peritonitis (hazard ratio [HR]: 0.97 [0.88 – 1.07]). Diabetes (HR: 1.14 [1.01 – 1.28] and continuous ambulatory PD (HR: 1.13 [1.04 – 1.23]) were significantly associated with a higher risk of peritoneal infection whereas nurse-assisted PD was associated with a lower risk of peritonitis (HR: 0.85 [0.78 – 0.94]. In the analysis restricted to the 3, 840 self-care PD patients, there was no association between age older than 75 years and risk of peritonitis. Conclusion: The risk of peritonitis is not increased in elderly patients on PD in a country where assisted PD is available.